KARAKTERISTIK DAN STATUS KESEHATAN JAMAAH HAJI KABUPATEN BANYUWANGI TAHUN 2012 - Wahjudi, Pudjo; Putriana, Maya Fahmi (FKM - UNEJ, 2014)
The number of Indonesiaâs pilgrim in 2012 estimated 200.000 persons, in general mostly of them were oldest with many health problems. This condition, many oldest pilgrims with many health problems also happened at the pilgrims of Banyuwangi District. The research objective are identified the caracteristic (sex, age, occupatiion, education, pilgrims experince) and the health status the pilgrims at Banyuwangi District by the year 2012. Type of this research is qualitative descriptive, by used secondary data from District Health Office and Ministry of Religion of Banyuwangi District. The result of this research showed that the characteristic of the pilgrims were the woman higher than man, largest age group among 40-49 and 50-59 years old, education background were elementary and occupational background were informal worker. The oldest pilgrims have high risk status related to health condition, mostly of them have the cardivascular disease (espescialy hypertension) and the endocrinal disease (especialy obesity and Diabetes Mellitus). Key words : pilgrims, characteristic, health status